Dari sakral menjadi komersial: perubahan nilai Taman Sriwedari Surakarta, 1910-1939 - Indriyani, Indriyani (Universitas Negeri Malang, 2025)
Abstract This research aims to analyze: (1) Relationship between the modernization of Surakarta and the commercialization of Sriwedari Park. (2) Realization of commercialization in Sriwedari Park. (3) Change of sacred values into commercial ones in Sriwedari Park. This research was conducted using historical methods. The sources used are primary and secondary sources, such as the Babad Taman Sriwedari, various article, and advertisements in contemporary newspapers, as well as relevant books. The research results show that: (1) Modernization of Surakarta had an impact on the development of people’s needs for entertainment facilities to fill their free time, then it makes Sriwedari Park changes from private space to public space through commercialization. (2) Commercialization of Sriwedari Park includes various spatial components and agendas within it, such as the Wayang Orang Sriwedari, Bioskop Sriwedari, Kebun Binatang Sriwedari, Malem Selikuran, Maleman Sriwedari, and Stadion Sriwedari. (3) Commercialization has the impact of changing the identity of Sriwedari Park, which was originially full of sacred traditional values becoming just an urban entertainment space.Abstrak Penelitian ini bertujuan untuk menganalisis: (1) Keterkaitan antara modernisasi kota Surakarta terhadap komersialisasi Taman Sriwedari. (2) Realisasi komersialisasi di dalam Taman Sriwedari. (3) Perubahan nilai-nilai sakral menjadi komersial di Taman Sriwedari. Penelitian ini dilakukan dengan metode historis. Sumber yang digunakan berupa sumber primer dan sekunder, seperti Babad Taman Sriwedari, berbagai artikel dan iklan dalam surat kabar yang sezaman, serta buku-buku cetak yang relevan. Hasil penelitian menunjukkan bahwa: (1) Modernisasi kota Surakarta berdampak pada berkembangnya kebutuhan masyarakat akan fasilitas-fasilitas hiburan untuk mengisi waktu luang, sehingga Taman Sriwedari kemudian mengalami perubahan dengan adanya komersialisasi dari ruang privat menjadi ruang publik. (2) Komersialisasi Taman Sriwedari meliputi berbagai komponen ruang dan agenda di dalamnya, seperti Wayang Orang Sriwedari, Bioskop Sriwedari, Kebun Binatang Sriwedari, Malem Selikuran, Maleman Sriwedari, dan Stadion Sriwedari. (3) Komersialisasi berdampak pada terjadinya perubahan pada identitas Taman Sriwedari yang semula sarat nilai-nilai tradisional sakral menjadi sekadar ruang hiburan perkotaan.